Analisis Prinsip-Prinsip dan Mekanisme Penyelesaian Sengketa WTO dalam Memastikan Keadilan Sistem Perdagangan Internasional Modern - Putri, Cinta Aisyah (Media Hukum Indonesia (MHI), 2026)
This article analyzes the principles and dispute settlement mechanisms implemented by the World Trade Organization (WTO) to ensure fairness and order in the modern international trade system. The study employs a normative juridical method with a conceptual approach based on secondary data. The results indicate that WTO’s fundamental principles, such as Most-Favoured Nation (MFN), National Treatment (NT), transparency, and predictability, play a crucial role in preventing trade disputes. Moreover, the dispute settlement mechanism through the Dispute Settlement Body (DSB) has proven effective, structured, and transparent in resolving conflicts among members, thereby strengthening the credibility and integrity of the global trading system. The synergy between WTO principles and the DSB mechanism provides a solid foundation for a fair, orderly, and predictable international trade environment.